Analysis on consumer recall, recognition and brand association of the Savlon Social Media Campaign - Rahman, Tanzeela (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.